Spectrophotometric Determination of Cefotaxime Sodium - Manohara, Y.N.; Srinivasa Rao, K.; Chandra Sekhar, M.; B.M. Gurupadayya, B.M. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods (A, B and C) have developed for the quantitative estimation of cefotaxime sodium in bulk drug and pharmaceutical preparations. Method A is based on the diazotization of cefotaxime sodium with nitrous acid and coupling with 2-naphthol to form red coloured chromogen with absorption maximum at 534 nm and Beer's law is obeyed in the concentration range of 20-100 μg/mL. Methods B and C are based on diazotization of cefotaxime sodium with nitrous acid and its coupling with phlorogucinol and resorcinol to form orange yellow and red coloured chromogen with absorption maxima at 464 and 513.5 nm, respectively. Beer's law is obeyed in the concentration range of 20-100 μg/mL and 10-50 μg/mL, respectively. The results obtained with the proposed methods are in good agreement with labelled amounts when marketed pharmaceutical preparations are analyzed. The results of analysis for the three methods have been validated statistically and by recovery studies. The results are compared with those obtained with UV spectrophotometric method at 234 nm.